Natural products exert anti-tumor effects by regulating exosomal ncRNA - Hu, Shuang; Liu, Yi; Guan, Shuguang; Qiu, Zhidong; Liu, Da (Frontiers in Oncology, 2022)
Currently, more than 60% of the approved anti-cancer drugs come from or are related to natural products. Natural products have multiple mechanisms of action in cancer therapy, among which regulation of exosomal non-coding RNAs (ncRNAs) to exert anti-cancer effects is of great research importance. Exosomes are a form of intercellular communication and contain ncRNAs that can act as intercellular signaling molecules involved in the metabolism of tumor cells. This paper summarizes the role played by active components of natural products in cancer prevention and treatment through the regulation of exosomal ncRNAs in recent years, and also introduces the biological effects of exosomes of natural origin themselves on cancer treatment, as well as the application of exosomes as natural drug delivery systems and biomarkers for predicting diseases in cancer prevention and treatment, providing new research ideas for the development of novel natural anticancer drugs.